Triploid twin gestation with single fetal demise associated with partial mole and pre‐eclampsia. Issue 4 (15th September 2017) - Okumura, Maria; Fushida, Koji; Francisco, Rossana Pulcineli Vieira; Schultz, Regina; Zugaib, Marcelo
Abstract: Both partial mole and twin gestation are conditions associated with the risk of the early onset of pre‐eclampsia. In cases of twin gestation, the death or selective termination of a severely growth‐restricted fetus may lead to the reversal of maternal pre‐eclampsia because of the involution or death of the pathological placenta, as has been reported by some authors. This case demonstrates that in a twin triploid gestation, in spite of the demise of one of the fetuses, the respective partial molar placenta can continue to grow and may contribute to the development or to the worsening of the pre‐eclampsia.